The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fonc.2020.576565
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Molecular Mechanism and Potential Drugs for COL1A1 in Carboplatin-Resistant Ovarian Cancer

Abstract: Carboplatin resistance in ovarian cancer (OV) is a major medical problem. Thus, there is an urgent need to find novel therapeutic targets to improve the prognosis of patients with carboplatin-resistant OV. Accumulating evidence indicates that the gene COL1A1 (collagen type I alpha 1 chain) has an important role in chemoresistance and could be a therapeutic target. However, there have been no reports about the role of COL1A1 in carboplatin-resistant OV. This study aimed to establish the detailed molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The interaction between COL1 and cisplatin resistance has been indicated by Rekowski et al in ovarian cancer [26]. Also, Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis revealed that COL1A1 regulated carboplatin resistance of ovarian cancer cells through the "ECMreceptor interaction" and "focal adhesion" pathways [27]. In addition, pcCOL1A2 was found to reverse the effects of miR-29a-3p on GC cell proliferation and apoptosis [28].…”
Section: Discussionmentioning
confidence: 91%
“…The interaction between COL1 and cisplatin resistance has been indicated by Rekowski et al in ovarian cancer [26]. Also, Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis revealed that COL1A1 regulated carboplatin resistance of ovarian cancer cells through the "ECMreceptor interaction" and "focal adhesion" pathways [27]. In addition, pcCOL1A2 was found to reverse the effects of miR-29a-3p on GC cell proliferation and apoptosis [28].…”
Section: Discussionmentioning
confidence: 91%
“…Orai1 knockdown or calcineurin/NFAT pathway inhibitors reduced the PTH-induced NFATC1 nuclear translocation and the PTH-induced increase in COL1A1 expression. Studies from other groups have shown that COL1A1 participates in cell adhesion and motility in various diseases ( 39 41 ). Therefore, we used RNA-seq and bioinformatics analyses to find that COL1A1 transcriptome expression was increased in PTH-treated HUVECs ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…6d). This list of 34 genes includes components of ITGA and ITGB superfamily [42], laminins [43], fibroblast growth factors [44,45], collagens [22,46], insulin growth factors [47,48], EGFR [49,50], FN1 [22,[51][52][53], EPHA2 [54], TNC [55], SPP1 [55,56], and VTN [22,57].…”
Section: Increased Expression Of Genes Involved In Pi3k-akt Signaling...mentioning
confidence: 99%